Random amplified polymorphic DNA (RAPD) analysis of Ornithobacterium rhinotracheale strains isolated from chickens in Turkey - Ozbey, G; Ertas, HB; Muz, A (Czech Academy Agricultural Sciences, 2005)
Six field strains of Ornithobacterium rhinotracheale isolated from chickens in Elazig province located in the East of Turkey were typed by serotyping and random amplified polymorphic DNA assay using a random primer (OPG-11). Using the AGP test used for serotyping, serotype A was found to be the predominant serotype, only one strain was serotyped as serotype B. By RAPD assay, the tested ORT strains were found to have different RAPD profiles. In addition, the RAPD assay showed almost similar DNA profiles among the tested strains of the serotypes A, B, D and E. The strain of serotype C did give a different RAPD profile. Within strains of the same serotype (A), different profiles were found but the strain of serotype (B) had an identical profile as strains of serotype A. This study suggests that more genotypes of ORT strains are present within the same serotype and thus that no relationship exists between the RAPD pattern of ORT and their serotype.
Keywords: Ornithobacterium rhinotracheale; random amplified polymorphic DNA; chicken; typing